Human right to water and international economic law - Greco, Roberta (London ; New York : Routledge; Torino, Italia : G. Giappichelli Editore, 2022)
"This book discusses the international right to water and the liberalization of water services. It is concerned with the harmonization of the right to water with the legal systems under which liberalization of water services has taken or may take place. It assesses paths of harmonization between international human rights law and international economic law in this specific field. The issue of the compatibility between the fulfilment of the right to water and the liberalization of water services has been at the heart of a passionate public debate between opponents and advocates of the privatization of the utility. The book provides an unbiased analysis of different international legal regimes under which the liberalization of water services has occurred or is likely to occur, notably international investment law, international trade law, and European Union law, in order to assess whether the main features of the right to water can be guaranteed under each of these systems of law and whether there is space for prospective harmonization"--Publisher's description.
The Human Right to Water Under International Law -- The Liberalization of Water Services Under International Investment Agreements and the Human Right to Water -- The Liberalization of Trade in Water Services Under the GATS and the Human Right to Water.
Keywords: Right to water; Foreign trade regulation; International economic relations; BUSINESS & ECONOMICS / Business Law; BUSINESS & ECONOMICS / International / Economics